Rigiditas Birokrasi sebagai Patologi Administrasi Publik: Hambatan Transformasi Digital Pemerintahan di Indonesia - Sri Yulianti Mozin; Alfiyah Agussalim; Resti Uda’a; Juljia Aulia Dodi; Alirman Totamu; Syafina Syafina; Nadin Anandhita Djafar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Bureaucratic rigidity is a form of public administration pathology that remains a serious problem in Indonesian governance. The bureaucracy's rigid, hierarchical nature, slow decision-making, and resistance to change are major obstacles to the government's digital transformation process. Amidst the demands of the digital era, which prioritizes speed, transparency, and efficiency, an unadaptive bureaucracy actually slows down innovation in public services and erodes public trust in the government. This study aims to analyze bureaucratic rigidity as a disease in public administration and its impact on the implementation of digital transformation in Indonesia. The method used is a qualitative approach with a literature review. The results indicate that bureaucratic rigidity is caused by a conservative organizational culture, complicated regulations, and low human resource capacity to adapt to technology. Furthermore, a lack of system integration and weak transformational leadership exacerbate these conditions. Digital transformation is not merely a technological issue, but a paradigm shift in governance. Therefore, comprehensive bureaucratic reform is needed, including simplifying procedures, strengthening the digital competency of civil servants, and shifting the work culture to be more flexible and innovative. Thus, an adaptive and responsive bureaucracy can be realized as the foundation of an effective digital government that is oriented towards public services.